Plasmonic nanofluids based on gold nanorods/nanoellipsoids/nanosheets for solar energy harvesting. (1st November 2016) - Du, M.; Tang, G.H.
Highlights: Optical properties of nanofluids containing nano-rods/ellipsoids/sheets are studied numerically. The plasmon absorption peak can be improved by tuning particle shape. Blended nanofluids are proposed and show great improvement in solar energy harvesting. Abstract: Due to the localized surface plasmon resonance (LSPR) effect excited on the surface of metallic nanoparticles, plasmonic nanofluids have been used to improve the efficiency of direct absorption solar thermal collectors (DASC) as working fluids. In this study, optical properties of plasmonic nanofluids containing gold nanoparticles with different shapes, sizes, aspect ratios and concentrations are studied numerically. The results show that the LSPR of gold nanorods and nanoellipsoids can be improved by tuning the aspect ratio. Particle size has little effect on extinction coefficient. Nanosheets show a great potential in solar thermal conversion. To achieve a broad-band absorption in both visible and near-infrared spectral region at a low particle concentration, the gold blended nanofluids made up of 20% nanoellipsoids of AR = 2, 60% nanorods of AR = 5, and 20% nanosheets of l / h  = 7 are proposed according to the plasmon resonance absorption band. An enhancement in solar energy harvesting of 104% for the gold blended nanofluids is achieved compared to the gold sphere nanoparticles even at an extremely low concentration and small particle size, which overcomes the instability of nanofluids under high concentration.